Cutaneous relapse of an ampullary carcinoma: an unusual presentation. (3rd July 2012) - Lamarca, Angela; Martinez-Marin, Virginia; Feliu, Jaime
Abstract : This is the first ever reported case about a cutaneous relapse of small bowel adenocarcinoma. The ampulla of Vater is the area of the small bowel that presents more frequently malignant transformation, nevertheless ampullary adenocarcinomas are rare but aggressive diseases. However, distant metastases are infrequent. Cutaneous metastases constitute the 5.3% of skin tumours, and are usually found in the 12% of malignancies. Their management usually includes local treatment if they are unique and systemic treatment when they are multiple. Chemotherapy schemes used in ampullary adenocarcinoma are those used in cholangiocarcinomas, pancreas and tumours of the gallbladder; nevertheless, given the intestinal origin of these tumours combinations of capecitabine and oxaliplatin are commonly used.